Refugia Block Influence on Insect Pattern Visiting Polinator at Poncokusumo Apples Plantation, Malang - Arif Mustakim; Amin Setyo Laksono; Zaenal Kusuma (Natural B, Journal of Health and Environmental Sciences, 2014)
Pollination service in agroecosystems depends on several factors, including the land management systems used by farmers. The using of variety of wild plans as refugia area are expected to be an alternative habitat for pollinators insect in plants: Ageratum conyzoides, Ageratum hostionum, Commelina difussa and Capsicum frutescens This research aims to know the composition of pollinators insect visit of refuge block and analyze their patterns in apple plantation Poncokusumo village Malang. Direct observations of insect pollinators diversity, community structure insect pollinators and abiotic factors in Poncokusumo village. were conducted on August 2012 to December 2013. Sampling was taken in each refuge block in four times observation at 07.00, 09.00, 12.00 a.m. and 3.00 p.m. Analysis of potential insect pollinators of apple blossoms as obtained from the importance and value of diversity index (Shannon-Wiener). Bray Curtis Index was noted diversity index value of insect pollinators was 1,26. The similarity between refuge block was noted with Bray Curtis index of 0,93 %. Community structure of insect pollinators in refuge block dominated from genus Syrphidae (40) and Tabanidae (22). Analysis of environmental factors of temperature, humidity and light intensity on the abundance of insect pollinators showed a negative correlation with the R-square value of 64,7 %.